2023
DOI: 10.3390/ijerph20064838
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Meteorological Parameters and Seasonal Changes on Reporting Patients with Selected Cardiovascular Diseases to Hospital Emergency Departments: A Pilot Study

Abstract: (1) Background: So far, research results have confirmed the relationship between heat and cold stress, the fluctuations in atmospheric pressure and high relative humidity, and the vulnerability of patients with so-called “weather-dependent” diseases which could lead to death. This study aimed to determine the meteorological parameters, their interactions, and the seasonal changes of the most significant factors in predicting the number of patients reporting to the Emergency Departments (EDs) in Poznań (Poland)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Scholars in China and around the world have used techniques such as correlation analysis, time series methods, and case crossover methods to study the relationships among meteorological conditions, air quality, and the onset of hypertension. It has been shown that meteorological conditions and air quality are important factors that induce the occurrence and development of CVDs such as hypertension, and the impact on the disease is long-term and extensive [3][4][5][6][7][8][9][10][11][12][13]. The 24, 48, and 72 h cold waves all had effects on the hospital admissions for hypertension on single-lag 5 d, and the effects of the 24 and 48 h cold wave were stronger (OR = 1.218, 95% CI: 1.072-1.385) in Jinchang, Gansu Province [14].…”
Section: Introductionmentioning
confidence: 99%
“…Scholars in China and around the world have used techniques such as correlation analysis, time series methods, and case crossover methods to study the relationships among meteorological conditions, air quality, and the onset of hypertension. It has been shown that meteorological conditions and air quality are important factors that induce the occurrence and development of CVDs such as hypertension, and the impact on the disease is long-term and extensive [3][4][5][6][7][8][9][10][11][12][13]. The 24, 48, and 72 h cold waves all had effects on the hospital admissions for hypertension on single-lag 5 d, and the effects of the 24 and 48 h cold wave were stronger (OR = 1.218, 95% CI: 1.072-1.385) in Jinchang, Gansu Province [14].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, CBC-derived ratios, such as the NLR (neutrophil to lymphocyte ratio) and PLR (platelet-to-lymphocyte ratio) have been proposed as useful alternative inflammatory biomarkers which can be potentially used for the diagnostic and prognostic assessment of various medical conditions such as cardiovascular, neurological, autoimmune, neoplastic and psychiatric diseases [8][9][10][11][12][13]. The effects of meteorological parameters on human health is widely studied, but mostly with regard to specific pathological conditions, such as seasonal infections [14], cardiovascular diseases [15,16], autoimmune diseases [17,18], neurological diseases [19,20] and mental disorders [21,22], allergies [23,24] and dermatitis [25,26]. There are quite a few studies which aim to determine the association between meteorological parameters and inflammation as the baseline of most pathologies [27,28].…”
Section: Introductionmentioning
confidence: 99%